The Origin of Improved Electrical Double‐Layer Capacitance by Inclusion of Topological Defects and Dopants in Graphene for Supercapacitors. (4th October 2016) - Chen, Jiafeng; Han, Yulei; Kong, Xianghua; Deng, Xinzhou; Park, Hyo Ju; Guo, Yali; Jin, Song; Qi, Zhikai; Lee, Zonghoon; Qiao, Zhenhua; Ruoff, Rodney S.; Ji, Hengxing
Abstract: Low‐energy density has long been the major limitation to the application of supercapacitors. Introducing topological defects and dopants in carbon‐based electrodes in a supercapacitor improves the performance by maximizing the gravimetric capacitance per mass of the electrode. However, the main mechanisms governing this capacitance improvement are still unclear. We fabricated planar electrodes from CVD‐derived single‐layer graphene with deliberately introduced topological defects and nitrogen dopants in controlled concentrations and of known configurations, to estimate the influence of these defects on the electrical double‐layer (EDL) capacitance. Our experimental study and theoretical calculations show that the increase in EDL capacitance due to either the topological defects or the nitrogen dopants has the same origin, yet these two factors improve the EDL capacitance in different ways. Our work provides a better understanding of the correlation between the atomic‐scale structure and the EDL capacitance and presents a new strategy for the development of experimental and theoretical models for understanding the EDL capacitance of carbon electrodes.